Compendium of documents and reports relating to the work of the UNCTAD Ad Hoc Working Group on the Interrelationship between Investment and Technology Transfer (UN New YorkUS, 1995)
Presents the final report of the work of the UNCTAD Ad Hoc Working Group as well as supporting documents which include the summaries of 19 country case-studies, a number of reports prepared by the UNCTAD Secretariat and the report of the Workshop on Environmentally Sound Technologies.
DC